Investigation of biomarkers regarding their predictive value in the development of gestational diabetes mellitus. An overview - Lazarou, Eleftheria; Lambrinou, Ekaterini; Kolokotroni, Ourania; Metallinou, Dimitra; Miltiadous, Panagiota; Hadjigeorgiou, Eleni (My University, 2023)
Introduction: Gestational diabetes mellitus (GDM) has been associated with various short- and long-term adverse perinatal outcomes for both mothers and their offspring. Its incidence is estimated to be 14% of all pregnancies worldwide. GDM screening and diagnosis delay as they take place between the 24th and 28th week of gestational age. Discordance among GDM diagnostic criteria has increased research interest regarding biomarkers since they may provide useful information when clinical and laboratory findings are still lacking. The present review provides evidence through an overview of biomarkers investigated in the blood of pregnant women early in pregnancy who subsequently developed GDM. Material and Methods: PubMed and Google Scholar were searched for articles published between 2010 – 2023. Key words ‘’gestational diabetes mellitus’’, ‘’biomarkers’’, ‘’biochemical markers’’, ‘’blood’’, ‘’serum’’, ‘’pregnancy’’, ‘’prediction’’ were used to identify relevant articles. Results: Totally, 12 studies were included. Sex hormone binding globulin (SHBG), Osteocalcin, Follistatin-like 3 (FSTL3), Malondialdehyde (MDA), Glutathione Peroxidase Activity (GPA), Triglyceride, YKL-40, microRNAs, plasma-glycated CD59 (pGCD59), Irisin and Ferritin have been investigated early in pregnancy in the blood of pregnant women who subsequently developed GDM. Osteocalcin, pGCD59, MDA, GPA, microRNA-16-5p, -17-5p and -20a-5p demonstrated higher levels in the serum of GDM-women compared to non-GDM while SHBG, Irisin and FSTL3 demonstrated lower levels. No association was found between YKL-40 serum levels and the early identification of women at risk for GDM. Conclusions: Several potential biomarkers with promising results relating to GDM predictive value have been explored in the blood of pregnant women during early pregnancy. However, currently, an ideal biomarker does not exist. As a result, further research is needed on this topic.
Keywords: Gestational diabetes mellitus; Pregnancy; Biomarkers; Prediction